Association of oestrogen-containing contraceptives with pulmonary lymphangioleiomyomatosis in women with tuberous sclerosis complex – Findings from a survey. (February 2014) - Sauter, Matthias; Sigl, Jannina; Schotten, Klaus-Jürgen; Günthner-Biller, Margit; Knabl, Julia; Fischereder, Michael
Abstract Objectives About 30–40% of women with tuberous sclerosis complex (TSC) develop pulmonary lymphangioleiomyomatosis (LAM). Oestrogen seems to be involved in LAM pathogenesis and oestrogen-containing contraception should be avoided in women with known LAM. However, there is very little data on the use of contraceptives in TSC patients. Methods We conducted a survey on the use of contraception and disease characteristics. The questionnaire was forwarded to all adult female TSC patients listed in the database of a German patient organisation. Results Data from 39 such patients could be analysed. Of these, 15 were diagnosed with LAM. Twenty-five patients (65%) confirmed current or past use of oestrogen- containing contraceptives. We found a suggestive correlation between the history of oestrogen-containing contraception, and LAM (Odds ratio: 6.500; 95% confidence interval: 1.199–35.230). However, oestrogen use was not associated with LAM complications. Conclusions Based on our findings, oestrogen-containing contraceptives should be resorted to by these patients only with great caution, and avoided whenever possible.